The influence of angle-specific torque of the knee flexors and extensors on the angle-specific dynamic control ratio in professional female soccer players. Issue 11 (3rd June 2022) - Eustace, Steven James; Morris, Rhys; Tallis, Jason; Page, Richard Michael; Greig, Matt
ABSTRACT: The purpose of this study was to assess whether dynamic torque ratios (DCR) from isokinetic strength assessments of eccentric knee flexors (eccKF) and concentric knee extensors (conKE) display differences when stratified into specific angle-specific DCR (DCRAST ) groups. Fifty-two professional female soccer players (age 21.30 ± 4.44 years; height 166.56 ± 5.17 cm; mass 61.55 ± 5.73 kg) from the English Women's Super League completed strength assessments of both lower limbs on an isokinetic dynamometer at 60°∙s −1. Angle-specific torque (AST) were used to calculate DCRAST to create sub-groups using clustering algorithms. The results identified for the dominant side that the Medium DCRAST group elicited significantly higher conKE AST when compared to Low and High DCRAST groups at increased knee extension ( P ≤ 0.05). For the non-dominant side, the High DCRAST group had significantly higher and lower eccKF and conKE AST compared to the Low DCRAST group at increased knee extension ( P ≤ 0.05). This study highlights that the inclusion of AST data may subsequently help practitioners to prescribe exercise that promotes strength increases at targeted joint angles. In turn, these approaches can be used to help reduce injury risk, identify rehabilitation responses and help inform return to play.